The important role and performance of engineered barriers in a UK geological disposal facility for higher activity radioactive waste. (July 2021) - Marsh, Ashley I.; Williams, Laurence G.; Lawrence, James A.
Abstract: The effective management of radioactive waste is a necessary prerequisite to the use of nuclear energy. The UK's policy for the long-term management of higher activity radioactive waste (HAW), and potentially spent nuclear fuel (SNF), is disposal in a deep underground geological disposal facility (GDF). A GDF will isolate HAW from mankind until the radioactivity has decayed to levels where any risk to future generations is acceptably low. It is likely, therefore, that a GDF will need to safely contain radioactive materials for hundreds of thousands of years. The necessary isolation will be provided by a combination of natural (geological) and engineered barriers. A multi-layered engineered barrier system will provide the defence-in-depth that is required to give the public confidence in the long-term performance of the GDF. This paper identifies the significant role each engineered barrier or "layer" plays in ensuring that long-lived radionuclides remain isolated from the biosphere and receptors within the vicinity of a GDF. Receptors include human and animal populations, and the natural environment. The paper also explores the characteristics and performance of a number of suitable candidate materials for use in the UK GDF engineered barriers. An indication of the lifetime of potential barriers under conditions pertinent to each of the UKs proposed geological settings is given. As the performance of the engineered barriers will be vital to the GDF post-closure safety case, several areas for further work are proposed. Graphical abstract: Image 1 Highlights: UK radioactive waste will be disposed of in a geological disposal facility (GDF). Radionuclides may be contained for a period of up to 3 million years by a GDF. The engineered barriers employed are highly dependent on the wasteform and geology. Barriers may serve multiple roles e.g. backfill, redox control, pH buffering etc. These roles are critical to ensuring radionuclide release is minimised.